1984 : the graphic novel - Nesti, Fido, 1971- (Houghton Mifflin Harcourt, 2021)
One of the most influential books of the twentieth century gets the graphic treatment in this first-ever adaptation of George Orwell's 1984. Orwell's best-known work of unrelenting dystopian realism warns against totalitarianism. The story is told from the point of view of Winston Smith, a functionary of the Ministry of Truth whose work involved the "correction" of all records each time the "Big Brother" decided that the truth had changed.